First examination of varying health outcomes of the chronically homeless according to Housing First configuration - Elizabeth Whittaker; Timothy Dobbins; Wendy Swift; Paul Flatau; Lucinda Burns (Elsevier, 2017)
Abstract Objective: To determine whether two Housing First configurations (scattered site [SS] versus congregated site [CS]) are associated with different health‐related outcomes. Methods: This ecological study employed a longitudinal, quantitative design to compare the outcomes from 63 individuals (SS: n=37; CS: n=26) in Sydney, Australia, over 12 months. Results: Both configurations showed similar improvements in quality of life and psychological distress. While recent use of substances remained stable across the two configurations over time, a marginally greater increase in the proportion of CS individuals injecting more than weekly was found. For health service utilisation, CS participants had notably higher service utilisation rates for mental health specialists and the emergency department for mental health reasons at follow‐up than SS participants. Conclusion: Preliminary evidence of differential injecting and health service utilisation outcomes between configurations emerged within this small‐scale study over the 12‐month period. Implications for public health: Given the rapid expansion of both SS and CS Housing First configurations across Western countries and the indications from this initial study that outcomes may differ according to configuration, there remains a need for robust evaluative evidence on the efficacy of various supported housing models on long‐term individual outcomes.